Patologi Birokrasi dalam Pelayanan Publik: Studi Literatur terhadap Dampak dan Upaya Penanggulangannya - Alshadiqa, Salma Afal; Ningsih, Rista; Wahyuni, Rina; Slipilia, Intan (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to examine the forms of bureaucratic pathology that occur in public services in Indonesia, as well as to analyze their impact on service quality and formulate strategies for overcoming them. This study uses a literature study method with a qualitative descriptive approach. Data were obtained from various relevant scientific articles, books, and research reports, especially those published between 2021 and 2024. The results of the study show that bureaucratic pathology in Indonesia is still systemic and complex, including corrupt practices, slow and discriminatory services, complicated procedures, and low transparency and accountability. Bureaucratic pathology has a significant impact on the declining quality of public services and public trust in the government. To overcome this, comprehensive bureaucratic reform is needed through simplifying procedures, increasing the capacity of the apparatus, transforming organizational culture, and consistently implementing the principles of good governance.